An Empirical Study to Identify the Barriers affecting Green supply Chain Management Implementation With Reference to Manufacturing Firms of Gujarat (International Journal of Food and Nutritional Sciences, 2022)
To focus on environmental challenges, manufacturing companies recently adopted green supply chain management. Industries are struggling to identify green supply chain management implementation challenges. This report identifies procurement-based hurdles to Green SCM deployment. Through literature, expert interviews, and a questionnaire survey from diverse industry sectors, 21 impediments were found.